Students' Perceptions of Online Learning at the Universitas Terbuka - Lenggogeni, Putri; Ambiyar, Ambiyar; Aziz, Ishak (Postgraduate School, Universitas Negeri Padang, 2024)
This research aims to evaluate student perceptions of the online learning experience at the Universitas Terbuka, focusing on its impact on student satisfaction, active involvement, and achievement of learning outcomes. Educational program evaluation methods are used to detail and analyze various aspects of perceptions that emerge during the online learning experience. This research involved the active participation of students from various study programs at the Universitas Terbuka. Data collection was carried out through surveys, in-depth interviews, and analysis of student reflections on online learning experiences. The evaluation results are aimed at providing in-depth insight into the extent to which online learning meets student expectations, the obstacles faced, and suggestions for improving the quality of online learning in an Universitas Terbuka environment. It is hoped that the results of this research will provide valuable information for the Universitas Terbuka in developing online learning strategies that are more effective and responsive to student needs. This evaluation focuses not only on technical aspects but also on dimensions of students' personal and academic experiences, creating a holistic educational program evaluation framework.